Effectiveness of Administrative Sanctions in Overcoming Fraud by Health Facilities on JKN Participants - Purnomo Purnomo; Zainal Arifin Hosein (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study discusses the effectiveness of implementing administrative sanctions to overcome fraud practices by health facilities against National Health Insurance (JKN) participants in Indonesia. Fraud practices involving claim manipulation, bill inflation, and falsification of diagnoses result in losses for JKN participants and reduce the quality of health services. This study identifies challenges in supervision, regulatory weaknesses, and obstacles in law enforcement that affect the effectiveness of the administrative sanctions imposed. Based on the analysis, this study recommends regulatory reforms that include the implementation of stricter sanctions, strengthening supervision with information technology, and increasing outreach programs to raise awareness of the impacts of fraud. It is expected that with this reform, the JKN system can run more effectively and reduce fraud practices that are detrimental to all parties.